Geobacillus stearothermophilus ATCC 7953 spore chemical germination mechanisms in model systems. (April 2015) - Georget, Erika; Kushman, Asel; Callanan, Michael; Ananta, Edwin; Heinz, Volker; Mathys, Alexander
Abstract: Bacterial endospores through their strong resistance to both chemical and physical hurdles constitute a risk for food industry. Inactivation strategies are based on thermal and/or chemical treatments but rely on incomplete knowledge of the mechanisms of inactivation. Alternative strategies were suggested to achieve food safety while improving product quality. One of them relies on the successive germination and inactivation by pasteurization of bacterial spores. However, to date, a gap of knowledge on bacterial spore germination remains and hinders such an application for food sterilization. Geobacillus stearothermophilus ATCC 7953 spore germination mechanisms were investigated by in situ fluorometry combined with plate counts. G. stearothermophilus spores' inner membrane was stained with Laurdan fluorescent dye. While nutrient pathways showed no strong germination with the combinations tested, successful germination up to 3 log10 could be achieved using 60 mmol l −1 calcium-dipicolinic acid (CaDPA) at 55 °C for 2 h. A model for the CaDPA germination mechanism in two phases could be derived which suggested a potential key role of cortex fragments in the germination path, before completion of the cortex degradation. Additionally, it was confirmed that the germination potential of CaDPA, which does not rely on nutrient receptors, is a widespread germination trigger across spore formers. Understanding germination mechanisms and the limitations of different germination paths is important for the development of multi-hurdle approaches to achieve commercial sterility with reduced thermal load. Highlights: Bacterial spores are a major concern for commercial sterility and food safety. Several chemicals can trigger endospores germination, leading to heat sensitization. Successful germination up to 3 log10 could be achieved with CaDPA 60 mM at 55 °C. Germination was associated to a phase change in the inner membrane. A two phase model for CaDPA germination was derived.